Electrolyte imbalances and their impact on outcomes in critically ill children: a prospective study from North India - Vishnoi, Dakshata; Rathoria, Ekansh; Singh, Saurabh Kumar; Srivastava, Mridula; Rathoria, Richa (International Journal of Contemporary Pediatrics, 2025)
Background: Electrolyte imbalances are frequent in critically ill children and significantly influence prognosis, yet pediatric data from North India remain scarce. To determine the prevalence of electrolyte imbalances in a tertiary care pediatric intensive care unit (PICU) and assess their associations with morbidity, mortality and clinical outcomes. Methods: This prospective observational study included 196 children (1 month–18 years) admitted to a North Indian tertiary PICU over 18 months. Electrolyte levels were measured at admission and monitored daily. Associations between dyselectrolytemia and outcomes including ventilatory and inotropic needs, complications, length of stay and mortality were analyzed using chi-square tests. Results: Electrolyte imbalance was observed in 58.2% of patients, with hyponatremia (52.6%) being most common, followed by hypocalcemia (13.8%) and hyperkalemia (7.1%). Dyselectrolytemia was significantly associated with prolonged PICU stay (p<0.0001), need for ventilation and inotropes (p<0.0001), complications (42.9%), MODS (11.2%) and higher mortality (p<0.0001). Seizures were the most frequent complication (20.4%). Mortality was highest with hyperkalemia (78.6%), followed by hypernatremia (57.1%) and hypokalemia (57.1%), whereas hyponatremia showed a non-significant trend. Overall mortality was 9.2%, lower than prior reports, possibly due to early monitoring and timely correction. Conclusions: Electrolyte disturbances are common in PICU and strongly associated with adverse outcomes. Hyperkalemia and hypernatremia carry the greatest mortality risk. Early recognition and prompt correction of dyselectrolytemia may reduce morbidity and improve survival. Larger multicentre studies incorporating additional electrolytes such as magnesium and phosphate are warranted.